Analysis of the Influence of Education, Economic Growth, Technological Development, and Wages on Unemployment on Java Island - Bagas Ricki Satrio; Yuni Prihadi Utomo (Proceedings International Conference on Sustainable Innovation (ICoSI), 2023)
The main and fundamental problem in Indonesia's labor force is the high unemployment rate. This is because the growth of new labor is significantly greater than the growth of available jobs each year. Labor growth that is greater than the number of available jobs results in an increase in unemployment. This study aims to measure the direction and magnitude of the influence of Education, Economic Growth, Technological Development, and Provincial Minimum Wage on the Open Unemployment Rate in Java Island for the period 2012-2021. This type of research data is secondary data in the form of panel data with the object of research on the Open Unemployment Rate in Java Island in 2012-2021, data obtained from the Central Statistics Agency (BPS). The analysis method used in this research is panel data regression analysis with the Random Effect Model (REM) selected model. The results showed that Economic Growth and Provincial Minimum Wage had a negative and significant effect on the Open Unemployment Rate, while Education and Technological Development had no effect on the Open Unemployment Rate. It is expected that the government should maintain the factors that influence economic growth and wages, as well as improve the education system and communication technology infrastructure. This research can be a reference for related parties in solving the problem of high unemployment in Java